Serving time or serving the community?: exploiting a policy reform to assess the causal effects of community service on income, social benefit dependency and recidivism - Andersen, Signe Hald (Journal of quantitative criminology, 2015)
Objectives There is a widespread belief among criminologists, judges and the like that criminals are better off serving non-custodial sentences instead of going to prison. However, empirical evidence of the effects of such other types of sentences is scarce. To help fill the gap, this paper assesses the causal effect of community service on post-sentence income, dependency on social benefits, and crime. Methods For the empirical analyses I exploit a policy reform that implemented the use of community service as punishment among specific groups of criminals, Danish administrative data, and difference-in-difference matching Results The results show that community service participants have higher long-run income levels and lower long-run levels of social benefit dependency compared to offenders who serve custodial sentences. However, while community service lowers recidivism among offenders convicted of violent crime, other traffic offences and misdemeanor, there are no overall effects of community service on crime committed after the serving of a sentence. Conclusions Serving a sentence through community services rather than in prison, causally improves offenders’ post-sentencing outcomes, particularly with regards to their labor market situation. Through this, the offender contributes not only to himself but also to society, and an increased use of non-custodial sentences is then beneficial on several levels. Importantly, my results apply to the Danish legal system, and may not be immediately applicable to other legal contexts.